المعالجة الصحفية لقضايا الاقتصاد المصري الموجهة لقراء الصحف دراسة تحليلية - نصر، محمد معوض إبراهيم; محمد، إبراهيم حسن المرسي; عبدالشافي، مؤمن جبر (جامعة عين شمس - كلية الدراسات العليا للطفولة, 2012)
تكتسب قضايا الاقتصاد المصري أهميتها الحيوية نظرا لارتباطها بمستقبل مصر ورفاهية شعبها، فالتغلب على القضايا الاقتصادية هو تحد صعب يجب اجتيازه لتحقيق التنمية الشاملة. وتعتبر معالجة هذه القضايا بأبعادها أمرا في غاية الأهمية وموضوعا يستحق الدراسة الجادة، ومعرفة هل قامت الصحف في أداء وظيفتها الأساسية وهي التصدي لقضايا المجتمع المصري وخدمة قضاياه الملحة والمؤثرة على مستقبله. وبات "الاقتصاد" عنصرا أساسيا على أجندة الأخبار في جميع وسائل الإعلام، ووجد القارئ نفسه محاصرا بمجموعة من الأحداث ذات الطابع الاقتصادي. وللإعلام الاقتصادي دور مهم في إدارة الأزمات المالية الاقتصادية من خلال استغلاله لكافة الفنون الصحفية لعرض وتبسيط المصطلحات الاقتصادية وتثقيف القارئ بالتطورات والتحولات الاقتصادية التي حدثت في السنوات الأخيرة. مشكلة الدراسة: تم تحديد مشكلة الدراسة على أن تكون على النحو التالي معالجة الصحف (القومية- والحربية- والخاصة) لقضايا الاقتصاد المصري. النتائج: توصلت الدراسة لمجموعة من النتائج أهمها: 1. مجموع الفنون الصحفية المختلفة التي عالجت قضايا الاقتصاد المصري بلغت (1879) فنا صحفيا، حيث جاءت جريدة الأهرم في الترتيب الأول بنسبة (36,3%)، ويأتي في الترتيب الثاني الوفد بنسبة (34.7%)، ثم المصري اليوم بنسبة (29%)، في حين احتلت المواد الإخبارية المرتبة الأولى بنسبة 77.2%، تلاها مواد الرأي بنسبة 13.7%، وأخيرا المواد الاستقصائية بنسبة 9%. 2. جاءت قضية الفساد في الترتيب الأول من بين قضايا الاقتصاد المصري (عينة الدراسة) بنسبة 43.5%، وجاءت صحيفة الوفد في مقدمة الصحف المصرية المهتمة بقضية الفساد بنسبة 20.3%، وتلاها الأهرام بنسبة 12.9%، ثم المصري اليوم بنسبة 10.3%. 3. جاءت قضية ارتفاع الأسعار في الترتيب الثاني من بين قضايا الاقتصاد المصري بنسبة 28%، وجاءت المصري اليوم في المقدمة بنسبة 10.6%، ثم صحيفة الوفد 8.9%، تلاها الأهرام 8%. 4. جاء في الترتيب الثالث قضية قضايا البطالة بنسبة 14.7%، جاءت الأهرام في المقدمة بنسبة 8.9%، ثم الوفد 3%، تلاها المصري اليوم 28%. 5. ثم جاء في الترتيب الرابع والأخير قضية الفقر بنسبة 13.8%، جاءت الأهرام في المقدمة بنسبة 5.1%، تلاها المصري اليوم 5%، ثم الوفد 3.8%. Journalistic treatment of the Egyptian economy-oriented newspaper readers- An analytical study Egyptian economy issues are of paramount importance vital as they relate to the future and well-being of the people of Egypt, Overcoming economic issues is a difficult challenge to go to achieve comprehensive development. The address these issues dimensions is extremely important and the subject deserves serious study, and find out whether the newspapers in the performance of its primary function is to address the issues of Egyptian society and its pressing issues and service affecting its future. The economy becomes a key element on the news agenda in all media, and reader found himself surrounded by a group of events of an economic nature. To inform an important economic role in the management of financial and economic, crises through the exploitation of all the arts journalist to view and simplify economic terms and educate the reader. Developments and economic transformations that have taken place in recent years. Problem of the study have been identified to be as follows treatment newspapers (national- and partisan- and private) to the issues of the Egyptian economy. The study of a group of important results: 1. Total Arts releases various addressed issues of the Egyptian economy hit (1879) art press, where it came from Al-Ahram newspaper in the first order by (36.3%), and comes in second delegation by (34.7%), then the Egyptian today by (29%). While news articles ranked first with 77.2%, followed by materials opinion by 13.7%, and finally materials survey by 9%. 2. The issue of corruption in the first place among the issues the Egyptian economy (sample) by 43.5%, came at the forefront of al-Wafd Egyptian newspapers interested in the question of corruption by 20.3%, followed by 12.9% Ahram, Egyptian then day by 10.3%. 3. The issue of rising prices in the second ranking among the issues the Egyptian economy by 28%, and Egyptian came today in the lead with 10.6%, then Al-Wafd 8.9%, followed by 8% Ahram. 4. Came in the third issue of unemployment issues by 14.7%, Al-Ahram led by 8.9%, then 3% delegation, followed by Al-Masry 2.8%. 5. Then came in the fourth and final issue of poverty by 13.8%, Al-Ahram led by 5.1%, followed by Al-Masry Al-5%, then 3.8% delegation.
Keywords: البطالة -- مصر -- الصحف اليومية -- المشاكل الاقتصادية -- التحليل الاقتصادي -- الأزمات المالية -- الفقر -- ارتفاع الأسعار